The origins of British bolshevism - Challinor, Raymond (London Totowa : Croom Helm Roman and Littlefield, 1977)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: bolsjewisme; communisme; socialisme; Groot-Brittannië.